Experimental and numerical studies of pressure and gap length effects on energy deposition in spark discharge - Korytchenko, K.V.; Varshamova, I.S.; Meshkov, D.V.; Dubinin, D.P.; Kovalenko, R.I.; Nazarenko, S.Yu. (Вопросы атомной науки и техники, 2021)
A study of the influence of the discharge gap length and the initial gas pressure on the energy deposition into the discharge channel was done. The study was conducted at the same total discharge energy. It is experimentally shown that the connection of the voltage probe to the discharge circuit significantly affects the discharge current. The determination of the energy deposited into the spark channel is based on the results of numerical simulation of the spark channel development. Experimentally measured discharge currents at different pressures and the gap length were used as initial data for the calculation. Based on the obtained results, it is determined which of the factors (the initial pressure or the gap length) has the strongest influence on the energy input into the spark channel.